Respuesta :
Simplifying
5x + 3 = 10x + -17
Reorder the terms:
3 + 5x = 10x + -17
Reorder the terms:
3 + 5x = -17 + 10x
Solving
3 + 5x = -17 + 10x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10x' to each side of the equation.
3 + 5x + -10x = -17 + 10x + -10x
Combine like terms: 5x + -10x = -5x
3 + -5x = -17 + 10x + -10x
Combine like terms: 10x + -10x = 0
3 + -5x = -17 + 0
3 + -5x = -17
Add '-3' to each side of the equation.
3 + -3 + -5x = -17 + -3
Combine like terms: 3 + -3 = 0
0 + -5x = -17 + -3
-5x = -17 + -3
Combine like terms: -17 + -3 = -20 -5x = -20
Divide each side by '-5'. x = 4
Simplifying x = 4
Combine like terms: -17 + -3 = -20 -5x = -20
Divide each side by '-5'. x = 4
Simplifying x = 4